2014
DOI: 10.1016/j.aoas.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Response of Prosopis Chilensis to biofertilization under calcareous soil of RasSudr. 2 – Pod production

Abstract: An experiment had been done in split design with 4 replicates in RasSudr Research Station, Desert Research Center, at South Sinai Governorate, Egypt, through 2009 on four years old Prosopis Chilensis to evaluate the effect of inoculation with Bradyrhizobium japonicum, Azotobacter chroococcum, Bacillus megatherium (PDB) and +VA mycorrhizae singly or in combination with vegetative (plant height, stem diameter and number of branches) and pod production (pod number/plant and pod weight/plant) and some chemical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…These results were in harmony with the finding by El-Gendy et al (2013) they showed that treated lemongrass (Cymbopogon citrates) with biofertilizer (nitrobein & rhizobacteria and microbein) with urea led to significant effect of flavonoid content in both seasons. This agreed with the result obtained by (Faramawy., 2014) reported that inoculation Prosopis chilensis with Bradyhizobium japonicum, Azotobacter chroococcum , Bacillus megatherium and VA mycorrhizal led to significantly increased total flavonoids.…”
Section: B) Effect Of Chemical Fertilization Bio-fertilizer and Tdz supporting
confidence: 93%
“…These results were in harmony with the finding by El-Gendy et al (2013) they showed that treated lemongrass (Cymbopogon citrates) with biofertilizer (nitrobein & rhizobacteria and microbein) with urea led to significant effect of flavonoid content in both seasons. This agreed with the result obtained by (Faramawy., 2014) reported that inoculation Prosopis chilensis with Bradyhizobium japonicum, Azotobacter chroococcum , Bacillus megatherium and VA mycorrhizal led to significantly increased total flavonoids.…”
Section: B) Effect Of Chemical Fertilization Bio-fertilizer and Tdz supporting
confidence: 93%
“…It is also well-known that B. megaterium produces organic, inorganic acids and CO2 which lead to an increase in soil acidity and consequently convert the insoluble forms of phosphorus into soluble ones [19]. As said by [20] the highest value of stem diameter was obtained by using the combined treatment between Brady+ Azoto + PDB+ AM as it recorded 15.2 cm on Prosopis chilensis. Seedlings inoculated with (Azotobacter chroococcum, Azospirillum brazilense and B. circulans) as soil inoculants gave significant increases in shoot length, root length and shoot dry weight when compared with control with the results obtained by [21] on Moringa oleifera.…”
Section: Resultsmentioning
confidence: 88%
“…As shown in Tables 5 and 6, the application of VAM, Azotobacter, and vermicompost improved the morphological characteristics compared to the control group. (Faramawy, 2014). Determining the optimum plant density could be critical for plant growth and yield.…”
Section: Discussionmentioning
confidence: 99%